Evaluation of the impact of the innovative potential of the companies from the SMEs sector on the efficiency of innovative actions: Suggestion of the evaluation method - Tomasz Norek; Leorardo Costa (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
The modern model for the innovative activity indicates that one of the key factors for success of innovative activity of enterprises is properly implemented the introduction of new solutions to market. It is widely recognized that the powers of innovation diffusion is an important determinant of the capacity of firms. The analysis of innovative activity of companies very often indicates that the innovations introduced to the market do not bring the expected benefits. This leads to the conclusion that very often innovation activities of enterprises are inefficient. This article is an attempt to examine relationship between the company's internal resources and the effectiveness of innovative activity. To achieve this research objective author formulated the hypothesis: (H1) There is the relationship between the company's internal resources and the effectiveness of innovative activity. This paper will present the results of empirical research conducted by the author among Polish SMEs in the years 2012 - 2014. The applied research method is based on the analysis of the innovative processes taking place in companies - with a special consideration of the nature of innovative processes taking place in SME sector companies.The author, using an online survey, conducted an empirical study of 200 SME sector companies (selection of companies was intentional - layered. The layers were: size of the company, the dominant type of business).In order to confirm hypotheses author applied the two-step analysis. The first step was the analysis of the innovation potential of the surveyed companies. This analysis allowed the precise determination of the factors affecting the innovation of enterprises. The second step was the analysis of the effectiveness of the innovative activity the surveyed companies. Summary of the study is to analyze the relationship between the company's internal resources and the effectiveness of innovative activity.
Keywords: 650; SME sector; Poland; innovation; efficiency of innovative